Anti-microbial activities of pomegranate rind extracts: enhancement by cupric sulphate against clinical isolates of S. aureus, MRSA and PVL positive CA-MSSA - Kelly Alison F; Fielder Mark D; Gould Simon WJ; Naughton Declan P (BMC, 2009)
Abstract Background Recently, natural products have been evaluated as sources of antimicrobial agents with efficacies against a variety of micro-organisms. Methods This report describes the antimicrobial activities of pomegranate rind extract (PRE) singularly and in combination with cupric sulphate against methicillin-sensitive and -resistant Staphylococcus aureus (MSSA, MRSA respectively), and Panton-Valentine Leukocidin positive community acquired MSSA (PVL positive CA-MSSA). Results PRE alone showed limited efficacy against MRSA and MSSA strains. Exposure to copper (II) ions alone for 2 hours resulted in moderate activity of between 102 to 103 log10 cfu mL-1 reduction in growth. This was enhanced by the addition of PRE to 104 log10 cfu mL-1 reduction in growth being observed in 80% of the isolates. However, the PVL positive CA-MSSA strains were more sensitive to copper (II) ions which exhibited moderate activities of between 103 log10 cfu mL-1 reduction in growth for 60% of the isolates. Conclusion PRE, in combination with Cu(II) ions, was seen to exhibit moderate antimicrobial effects against clinical isolates of MSSA, MRSA and PVL positive CA-MSSA isolates. The results of this study indicate that further investigation into the active ingredients of natural products, their mode of action and potential synergism with other antimicrobial agents is warranted. This is the first report of the efficacy of pomegranate against clinical PVL positive CA-MSSA isolates.